Root-based inorganic carbon uptake increases the growth of Arabidopsis thaliana and changes transporter expression and nitrogen and sulfur metabolism - Gamarra Reinoso, Liesel; Majláth, Imre; Dernovics, Mihály; Fábián, Attila; Jose, Jeny; Jampoh, Emmanuel Asante; Hamow, Kamirán Áron; Soós, Vilmos; Sági, László; Éva, Csaba (Frontiers in Plant Science, 2024)
Root-based uptake of inorganic carbon has been suggested as an additional carbon source. Our study aimed to characterize and understand the root-based uptake and fixation mechanisms and their impact on plant growth. 13C-labeled bicarbonate fed to Arabidopsis roots was assimilated into aspartic acid but mainly into sucrose, indicating that the added inorganic carbon was transported to the leaves. A hydroponic treatment was also established for A. thaliana using 2 mM NaHCO3 at pH 5.6, which enhanced the photosynthetic and growth parameters. According to transcriptome sequencing data, the observed enhancement in growth may be orchestrated by trehalose-6-phosphate signaling and supported by augmented nitrogen and sulfur assimilation. The analysis also revealed regulatory and transporter activities, including several nitrate (NRT2.1), and sulfate transporter (SULTR1;1 and SULTR1;2) candidates that could participate in bicarbonate uptake. Different transporters and carbon fixation mutants were assessed. A homolog of slow-type anion channel 1 (slah3) carbonic anhydrase (βca4), and sulfate transporter (sultr1;2) mutants were shown to be inferior to the bicarbonate-treated wild types in several growth and root ultrastructural parameters. Besides, aquaporin genes PIP1;3 and PIP2;6 could play a negative role in the carbon uptake by venting carbon dioxide out of the plant. The findings support the hypothesis that the inorganic carbon is taken up by the root anion channels, mostly transported up to the shoots by the xylem, and fixed there by RuBisCo after the conversion to CO2 by carbonic anhydrases. The process boosts photosynthesis and growth by providing an extra carbon supply.